Pengaruh Job Insecurity, Stress Kerja, Dan Lingkungan Kerja Terhadap Turnover Intention (Studi Pada Karyawan PT Bank Syariah Indonesia KC Padangsidimpuan) - Dio Rabintar Cupema Hasibuan; Kartini Harahap; Onan Marakali Siregar (Journal of Creative Power and Ambition (JCPA), 2024)
Human resources play an important role in advancing a company, especially banking companies such as Bank Syariah Indonesia (BSI) Padangsidempuan. Therefore, companies need to pay attention to the conditions experienced by employees, especially regarding career development and guarantees, mental state, and work atmosphere and facilities in order to form. However, the turnover rate in the company tends to be high in the past year, which can be seen from the greater number of employees leaving than entering the company. It was found that fear of career threats, giving workloads that are considered inadequate, and inadequate atmosphere and facilities are the causes of turnover in the company. The purpose of this study is to examine the relationship between the variables Job Insecurity, Work Stress, and Work Environment used to explain the occurrence of Turnover Intention phenomenon in employees at BSI Padangsidempuan. This study also aims to analyze the influence of the first three variables on the turnover process in the company. The study was conducted using a quantitative method with an associative approach. Data were collected by distributing questionnaires to 32 employees who were also the entire population of BSI Padangsidempuan supported by secondary data such as various books and previous studies. The data were then analyzed using instrument tests, classical assumption tests, multiple linear regressions, and hypothesis tests as data interpretation tools. The researchers found that the variables Job Insecurity, Job Stress, and Work Environment had a significant effect on changes in the Turnover Intention variable with a level of correlation and influence of 96.3% and 91.9%, respectively. The results of the study indicate that factors related to the three variables are the cause of employee turnover at BSI Padangsidempuan.